A Simple Approach for Prediction of the Condensed Phase Heat of Formation of Imidazolium‐Based Ionic Liquids or Salts. Issue 12 (30th March 2018) - Keshavarz, Mohammad Hossein; Nazari, Behzad; Jafari, Mohammad; Bakhtiari, Reza
Abstract: Solid or liquid (condensed state) phase enthalpy of formation of a desired new substance at room temperature is a measure of its energy content. It is an important factor for its designing, characteristics and thermochemical stability. A novel method is introduced for reliable prediction of the condensed phase heat of formation of imidazolium based ionic liquids or salts at 298.15 K. It is based on the number of hydrogen and fluorine atoms in cation and anion, respectively, as well as two correcting functions. The reported condensed phase heat of formation of 31 different imidazolium based ionic liquids or salts are used to derive new model. For 9 imidazolium based ionic liquids or salts where the outputs of complex quantum mechanical methods were available, reliability of the new model has been compared with their results. Root Mean Squared Error (RMSE) of the new model and quantum mechanical models are 25.02 and 31.80 kJ/mol, respectively, which confirm higher reliability of the new simple method. Abstract : A reliable new correlation has been provided for predicting the condensed phase standard enthalpy of formation of imidazolium based ionic liquids or salts. The number of hydrogen atoms in cation and fluorine atoms in anion as well as two correcting functions have been used for constructing the new model and its reliability has been checked by comparison of results with quantum mechanical methods, where their data were available.